SEED GERMINATION AND VIGOR OF Arctium lappa L. SEEDLINGS SUBJECTED TO ALUMINIUM TOXICITY - Silverio, Juliana Milene; Santos, Cleberton Correia; Bernardes, Rodrigo da Silva; Espíndola, Giselly Marques; Meurer, Hércules Lazari; Vieira, Maria do Carmo (Revista Brasileira de Engenharia de Biossistemas, 2021)
Aluminium (Al) in acid soils reduces the physiological potential of seeds and limits growth of several species of agronomic and medicinal interest. However, information on Al toxicity in Arctium lappa L. (burdock, Asteraceae) is scarce. The aimed of this study was to evaluate the effect of aluminium stress on germination and vigor of A. lappa seedlings. Five concentrations of hydrated aluminium sulfate Al2(SO4)3·16H2O: 0 (control), 5, 10, 15 and 20 mmol L-1 were tested. The germination test was performed in Gerbox boxes (on paper – SP) and in paper roll – RP, using germitest® paper wetted 2.5 times its dry wight. The seeds were kept in B.O.D. chambers, under 20-30 ºC and constant withe light. Physiological potential of the seeds and vigor was evaluated by tests of first germination count (4th day), germination (7th day) and seedlings length. We observed a reduction in germination as Al concentration increased on the substrate SP. The lower aerial part length of the seedlings occurred with 20 mmol L-1 Al and on the substrate SP. Occurred a root inhibition of seedlings as Al concentration increased in both substrates, especially on the SP. Aluminium stress and substrate SP negatively affected seeds germination and vigor of A. lappa seedlings.